Phosphatase POPX2 Exhibits Dual Regulatory Functions in Cancer Metastasis - Zhang, Songjing (2017)
Cancer metastasis is a complex mechanism involving multiple processes. Previously, our integrative proteome, transcriptome, and phosphoproteome study reported that the levels of serine/threonine phosphatase POPX2 were positively correlated with cancer cell motility through modulating MAPK signaling. Surprisingly, here we found that POPX2 knockdown cells induced more numerous and larger tumor nodules in lungs in longer term animal studies. Interestingly, our analysis of DNA microarray data from cancer patient samples that are available in public databases shows that low POPX2 expression is linked to distant metastasis and poor survival rate. These observations suggest that lower levels of POPX2 may favor tumor progression in later stages of metastasis. We hypothesize that POPX2 may do so by modulation of angiogenesis. Secretome analysis of POPX2-knockdown MDA-MB-231 cells using LC–MS/MS-based SILAC quantitative proteomics and cytokine array show that silencing of POPX2 leads to increased secretion of exosomes, which may, in turn, induce multiple pro-angiogenic cytokines. This study, combined with our previous findings, suggests that a single ubiquitously expressed phosphatase POPX2 influences cancer metastasis via modulating multiple biological processes including MAPK signaling and exosome cytokine secretion.